The Relationship Between Self-compassion and Mood in Iranian Patients with Heart Failure: A Cross-sectional Study. - Zolfaghari, Fatemeh; Babaei, Sima; Nazari, Fatemeh; Momeni-Ghaleghasemi, Tahere (Journal of Nursing & Midwifery Sciences, 2025)
Background: Heart failure, recognized as the final stage of cardiac disorders, significantly impacts various aspects of patients' lives. Given the high prevalence of this disease and its psychological effects, examining psychological factors such as self-compassion is of particular importance. Objectives: The present study aimed to assess the role of self-compassion in improving mood states in heart failure patients. Methods: In this cross-sectional, descriptive correlational study, the relationship between self-compassion and mood states was examined in 200 heart failure patients hospitalized at Chamran Hospital in Isfahan in 2023 using a convenience sampling method. The sampling process was carried out over a three-month period, from October to December 2023. Data were collected using the Profile of Mood States (POMS) and Self-compassion Scale (SCS) questionnaires and analyzed using SPSS version 25. Correlation coefficients and multiple linear regression were used for data analysis. Results: The results showed that most patients were aged 51 - 60 years, male, married, and had primary education. The mean total score for self-compassion was 76.33, and the mean total score for mood states was 95.6. A significant negative correlation was observed between mood states and self-compassion, indicating that as self-compassion increases (correlation coefficient: -0.33, P < 0.001), mood states improve. Additionally, linear regression results showed that self-compassion could predict mood states. The Beta value for self-compassion was -0.33 (P = 0.001, β = -0.33), indicating that an increase of one standard deviation in self-compassion would result in a 0.33 standard deviation decrease in mood states. Therefore, as self-compassion increases, mood states improve. Conclusions: Based on the results of this study, it can be stated that self-compassion is significantly associated with improved mood states in heart failure patients and can predict mood states. It is recommended that managers and nurses enhance self-compassion in patients to improve their mood states. These findings emphasize the importance of considering psychological factors in improving the condition of heart failure patients.